A star is born again: Methods for larval rearing of an emerging model organism, the False clownfish Amphiprion ocellaris. Issue 4 (4th February 2021) - Roux, Natacha; Logeux, Valentin; Trouillard, Nancy; Pillot, Rémi; Magré, Kévin; Salis, Pauline; Lecchini, David; Besseau, Laurence; Laudet, Vincent; Romans, Pascal
Abstract: As interest increases in ecological, evolutionary, and developmental biology (Eco‐Evo‐Devo), wild species are increasingly used as experimental models. However, we are still lacking a suitable model for marine fish species, as well as coral reef fishes that can be reared at laboratory scales. Extensive knowledge of the life cycle of anemonefishes, and the peculiarities of their biology, make them relevant marine fish models for developmental biology, ecology, and evolutionary sciences. Here, we present standard methods to maintain breeding pairs of the anemonefish Amphiprion ocellaris in captivity, obtain regular good quality spawning, and protocols to ensure larval survival throughout rearing. We provide a detailed description of the anemonefish husbandry system and life prey culturing protocols. Finally, a "low‐volume" rearing protocol useful for the pharmacological treatment of larvae is presented. Such methods are important as strict requirements for large volumes in rearing tanks often inhibit continuous treatments with expensive or rare compounds. Abstract : To properly use anemonefish as a laboratory model species, it is required to have breeding pairs, husbandry with broodstock room, larval rearing tanks, and low‐volume rearing tanks for experimental purposes, and finally living prey cultures (nauplii of artemia, rotifers, and algae) Research Highlights: This paper describes how to set up a rearing system for anemone fishes at the laboratory scale as this species is becoming a relevant marine fish model to tackle Eco‐Evo‐Devo questions. We detail two rearing methods, one consisting of classical rearing conditions and the other one consisting of low‐volume conditions (500 ml).